Analysis of obstacles in teaching and learning nuclear physics: towards a digital approach in secondary education - Taoussi, Aziz; Chikhaoui, Ahmida; El Khattabi, Khalid; Yakkou, Hassan (Institute of Advanced Engineering and Science, 2025)
The study explores the specific obstacles encountered in the teaching and learning of nuclear physics within qualifying secondary schools in Morocco, particularly in the Fez-Meknes delegation. We identified a lack of specific research on this topic, despite a growing interest in improving science teaching. Using questionnaires administered to 100 teachers and 200 students, we found that the absence of laboratory experiments due to the dangers associated with nuclear physics is a major obstacle. Difficulties in understanding concepts such as radioactive decay, nuclear fusion, and fission were also noted. To overcome these challenges, we propose the development of digital teaching resources adapted to the Moroccan curriculum, including simulations and interactive tutorials. These resources are viewed positively by teachers and students alike, as they facilitate understanding of concepts, increase engagement and enable self-paced learning, promoting autonomy in learning and the development of creativity in students. For successful integration, it is essential to provide adequate training and ongoing support for teachers. The results offer concrete avenues for improving the quality of teaching in physical sciences and learning in a digital environment motivates students in Morocco.